Do insurers respond to active purchasing? Evidence from the Massachusetts health insurance exchange. Issue 1 (12th December 2022) - Shepard, Mark; Forsgren, Ethan
Abstract: Health insurance markets face continued challenges with high premiums and limited insurer competition. We describe a unique set of "active purchasing" policies used by Massachusetts' pioneer health insurance exchange to shape the rules of competition and reward lower‐price insurers with additional customers. We provide evidence that these policies significantly influenced insurer pricing. Between 2010 and 2013, over 80% of insurer prices were set exactly at or within 1% of pricing thresholds created by active purchasing policies. A key "limited choice" policy was associated with a 16%–20% reduction in average insurance prices relative to comparison markets in 2012–2014. Insurers achieved these price cuts partly through cost reductions via narrower provider networks and partly through reduced profit margins.